The concept of energy homeostasis for optimal health during training - Saris, W. H. (Canadian Journal of Applied Physiology, 2001)
From all nutritional variables optimal energy supply is considered as most vital for human performance. It is postulated that lack of energy homeostasis is the basic problem in the development of overtraining. Most if not all clinical symptoms are directly or indirectly related to the physiological mechanisms of energy homeostasis. The rapidly increasing knowledge in the field of body weight control with several new regulatory neuro-peptides such as leptin, will give new opportunities to tackle this unbalance between training load and energy availability. The central role of leptin and insulin as adiposity signals has focussed attention on the anti-obesity aspects of leptin. However as member of the cytokine family, leptin is also closely linked to the immune and reproductive system. New data indicates clearly the dual function of leptin at both ends at the energy balance; starvation vs. overfeeding. It links also nutrition to the reproductive system. Lack of available energy has a much greater impact on leptin levels than exercise stress. It is suggested that application of the rapidly increasing knowledge in the obesity field will benefit the research on the mechanisms involved in the derailment of the delicate balance between training load and energy homeostasis in athletes.